INCREASING STOCK PRICES : THE ROLE OF LEVERAGE AND DIVIDEND POLICY - Muspa Muspa (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
Abstract : This study aims to determine the role of leverage and dividend policy in increasing stock prices. The stock price is important because it can be used to assess the condition of a company and become a reference for investors to invest in the company. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The sampling technique used purposive sampling method in order to obtain 230 manufacturing companies. All data is processed using Structural Equation Modeling analysis based on Partial Least Square. The results of this study indicate that leverage has a positive effect on dividend policy. In addition, leverage and dividend policy have a positive effect on stock prices. Or stated, the dividend policy succeeded in mediating the effect of leverage on stock prices. Keywords: Leverage, Dividend Policy, Stock Prices